Nutritional and phytochemical properties of Chaya leaves (Cnidoscolus chayamansa Mc Vaugh) planted in Northeastern Thailand - Kongphapa, Juthamas; Chupanit, Pornpimol; Anutrakulchai, Sirirat; Cha’on, Ubon; Pasuwan, Patimakorn (Asia-Pacific Journal of Science and Technology, 2021)
Chaya (Cnidoscolus chayamansa Mc.Vaugh) is commonly found in Thailand, especially in the northeastern (Isan) region where the consumption of this plant has been cooked for its nutritional benefits and taste. To assess the nutritional composition and antioxidant properties of raw and cooked chaya leaves. Chaya plants from Isan were heat-treated by boiling and drying and compared with raw leaves. Analysis of nutritional composition, phenolic compounds, total phenolic content (TPC) and antioxidant capacity were standardized techniques. Cooked leaves showed a significant (p≤0.05) decrease in protein, carbohydrate, potassium, sodium, and hydrocyanic acid compared to raw leaves. Chaya leaves are rich in protein (32.41-34.02 g/100g dry weight), but the preliminary protein quality by a digestible indispensable amino acid score is low with isoleucine being the limiting amino acid. Cooking was also significantly (p≤0.05) eliminated hydrocyanic acid (HCN) Raw (1121.72), Cooked (1.71) mg/kg dry weight]. The major phenolic compounds of both samples were sinapic acid and caffeic acid. Cooked leaves have TPC decreased significantly (p ≤ 0.05). TPC and antioxidant capacity are significantly (p ≤ 0.05) decreased by three assays. The results proved that chaya plants found in Thailand are rich sources of nutritional and phytochemical properties. Some plants must require a heat-treated process for safe consumption. Although, some nutritional and phytochemical properties diminish.